A study about expectations of the athletes from their coaches resting in Olympics preparation camping Gaziantep - Huseyin Ozturk; Idris Cıldır; Omur Avsar (Türk Spor ve Egzersiz Dergisi)
This is a descriptive study, aims to specify the expectations of the athletes from their coaches resting in Olympic Preparation Camp. A total of 120 athletes resting in Olympic Preparation Camp in Gaziantep participated the research including 94 men and 26 women. The expectation scale (ASABÖ, 2008) was used for collecting the data of this research which was used in scientific study done by Güzel before (7). The scale consist of three sub-dimensions; behavior, coaching model and personality. SPSS 16.0 package was used for statistical analysis of the study and p lt;0.05 level is accepted as meaningful. Subsidiary statistical methods used in analyzing data (Frequency, percentage, average, Standard deviation). In analyzing of hypothesis, unbiased sample independent sample t-test and One way Anova test were used. Study results revealed that the athletes are mostly 16-18 age range; prefer wrestle and weight lifting as branches and they are graduate from secondary school or high-school. Besides having confidence in athletes, being honest with them and respect to them, not discriminate among them and knowing their personality traits and relationships between each other and also acting consistently and to be open to criticism are highly expected behaviors from the coaches.